Structural studies on determinants of receptor/ligand binding in the tumour necrosis factor and T cell receptor protein families - Marles-Wright, J (2005)
Protein-protein recognition plays a central role in the surveillance of self and non-self in the mammalian immune system and ultimately in cellular survival within the organism. Two systems of fundamental importance to the immune system are the Tumour Necrosis Factor (TNF) and the T cell receptor (TCR) families. High-throughput methods developed within the Oxford Protein Production Facility have been successfully applied to the production of members of the TNF receptor and ligand superfamilies for structural characterisation. The TNF receptor DR6 was successfully refolded from E.coli inclusion bodies using a rapid-dilution technique and yielded diffraction quality crystals. Data collected from these crystals will be used to obtain an x-ray crystallographic model of DR6. Vascular Endothelial Growth Inhibitor (VEGI) was produced as a soluble recombinant protein in E.coli, and formed a number of poorly diffracting crystals, it is hoped that further trials and optimization of conditions will lead to improved data quality. Lymphotoxin β receptor was produced in a Eukaryotic system. This has shed light on the complications posed by signal peptide cleavage and glycosylation on the production of protein for crystallization trials. TNF superfamily proteins are ideal targets for the design of novel therapeutic agents due to their involvement in a number of disease pathologies. Various methods of molecular docking and small molecule design were applied to the search for potential inhibitors of receptor binding for the TNF ligand proteins TRAIL and BAFF. A number of potential drug leads were identified from the National Cancer Institute drug database. The Natural Killer (NK) T cell restricted TCRs recognise CD1d-presented glycolipid. Determination of the crystal structures of the invariant NK TCR and the NK restricted TCRs 5E and 5B shows that these proteins adopt the canonical structures of class I MHC restricted TCRs. This suggests that the binding of CD1d-glycolipid by these receptors will conform to the same model of binding seen for the class I MHC restricted TCRs.